Integrating Digital Media in Content-Based Language Teaching for English Specific Purposes: A Study of Online Learning Platforms in Reading Comprehension - Suhendra, Erwin; Rahmawati, Lela; Hastuti, Hilda; Syarifaturrahman, Wahyu Kamil (LPPM Universitas Bumigora Mataram, 2025)
This study investigates the integration of digital media in Content-based Language Teaching (CBLT) to improve reading comprehension in contexts involving English for Specific Purposes (ESP). Using a Classroom Action Research (CAR) design, the study was conducted over two cycles involving 79 undergraduate students from the Management Study Program at Universitas Bumigora. Digital media—including a Moodle-based Learning Management System (LMS), WhatsApp group discussions, and AI-generated video content–were implemented to support student engagement and content understanding. Quantitative data from pre- and post-tests revealed a significant improvement, with a mean score increase of 34.35 points (p < .001). Qualitative data from classroom observations indicated enhanced learner autonomy, increased peer collaboration, and better task engagement, particularly in the second cycle. The findings suggest that integrating digital platforms into ESP instruction improves comprehension and fosters student-centered learning environments. This study supports previous research on the pedagogical potential of digital media in language education and provides a practical model for embedding technology in higher education language classrooms.